A digital enzyme-linked immunosorbent assay for ultrasensitive measurement of amyloid-β 1–42 peptide in human plasma with utility for studies of Alzheimer's disease therapeutics. Issue 1 (December 2016) - Song, Linan; Lachno, D.; Hanlon, David; Shepro, Adam; Jeromin, Andreas; Gemani, Dipika; Talbot, Jayne; Racke, Margaret; Dage, Jeffrey; Dean, Robert
Abstract Background Amyloid-β 1–42 peptide (Aβ1–42 ) is associated with plaque formation in the brain of patients with Alzheimer's disease (AD). Pharmacodynamic studies of AD therapeutics that lower the concentrations of Aβ1–42 in peripheral blood require highly sensitive assays for its measurement. A digital enzyme-linked immunosorbent assay (ELISA) using single molecule array (Simoa) technology has been developed that provides improved sensitivity compared with conventional ELISA methods using the same antibody reagents. Methods A sensitive digital ELISA for measurement of Aβ1–42 using antibodies 3D6 and 21F12 was developed. Assay performance was evaluated by repeated testing of pooled human plasma and buffer diluent quality control samples to determine relative accuracy, intra- and inter-assay precision, limit of detection (LOD), lower limit of quantification (LLOQ), dilutional linearity, and spike recovery. The optimized assay was used to quantify Aβ1–42 in clinical samples from patients treated with the β-site amyloid precursor protein cleaving enzyme 1 inhibitor LY2886721. Results The prototype assay measured Aβ1–42 with an LOD of 0.3 pg/ml and an LLOQ of 2.8 pg/ml in plasma, calibrated using an Aβ1–42 peptide standard from Fujirebio. Assay precision was acceptable with intra- and inter-assay coefficients of variation both being ≤10%. Dilutional linearity was demonstrated in sample diluent and immunodepleted human plasma. Analyte spike recovery ranged from 51% to 93% with a mean of 80%. This assay was able to quantify Aβ1–42 in all of the 84 clinical samples tested. A rapid reduction in levels of Aβ1–42 was detected within 1 h after drug treatment, and a dose-dependent decrease of Aβ1–42 levels was also observed over the time course of sample collection. Conclusions This digital ELISA has potential utility in clinical applications for quantification of Aβ1–42 in plasma where high sensitivity and precision are required.